Moodle as An Online Learning Platform : What Teacher's Need to Prepare - Anna Nadhifatul Ilmiah; Meta Alifia Risty; Rizky Alifia Annisa; Sofie Abiyyati; Refi Ranto Rozak; Ima Isnaini Taufiqur Rohmah; Sirniawati Maskud (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Moodle was being the choice of teachers as a virtual learning media. The transition of learning from face-to-face learning to virtual learning or online learning forces teachers to deal with this situation. The preparation that a teacher must prepare become a huge thins to be understanding before conducted teaching and learning. A descriptive qualitative research was applied for this study. Interview and observation were obtained from the teachers to gain the teacher’s perspectives of moodle as an online learning platform. The result of this study found that the were some steps to be conducted to prepare the online learning using moodle: preparation, action, and evaluation.